Using Visio in visualization of business-process - Поморцева, Елена Евгеньевна (Eastern-European Journal of Enterprise Technologies, 2012)
The questions connected to duly acceptance of the correct organizational decision are considered. The large volumes of the information are significant difficulty in it. The program Visio enables to speed up process and to avoid the erroneous and wrongful decisions